POLA PERSEBARAN OUTLET AIR MINUM ISI ULANG DI KABUPATEN SEMARANG - Hardati, Puji (Jurnal Geografi, 2015)
The need for drinking water is increasing, along with the total population, while the presence of waterresources for drinking increasingly limited. This study aims to explain the pattern of distribution of drinkingwater refill outlets . Data analysis using descriptive method, served with tables and figures. In Semarangregency, in 2005 there were forty outlets refill drinking water, increased approximately doubled over the lastten years. increased almost doubled over the last tens years. The existence OAMIU located in severalvillages/wards, formed a pattern of random distribution, related to the accessibility of the area andpopulation agglomeration. Ungaran Barat subdistrict, became one of the areas that have the most numberOAMIU, such as central government, social, and economic population. The location strategy, where thehighway leading to the city of Yogyakarta, Solo (Surakarta) from Semarang (Joglosemar).